ANALISIS KETIMPANGAN WILAYAH BERDASARKAN PDRB DAN PAD ANTARA RIAU DARATAN DENGAN RIAU PESISIR - Mairisa '; Yusbar Yusuf; Hendro Ekwarso (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted in region Riau Mainland and Coastal Riau. The purpose of this study to determine the level of inequality region based on Gross Regional Domestic Product (GRDP) and the level of inequality region based Local Original Revenue(PAD) between region Riau Mainland and Coastal Riau of the year 2010-2015. This study uses secondary data, data that has been collected by the data collector agency and published to the user community of data. This data is sourced from the Central Statistics Agency of Riau Province, the data used in this study is data PDRB and data PAD 2010-2015. This research using quantitative descriptive method by describing and describing the data obtained as well as the calculation of the figures mathematically using analysis tool index entropy Theil. From the results of research based on entropy index Theil is known that, during a period of 6 years (2010-2015) inequality region Riau Mainland higher than the Coastal Riau based Gross Regional Domestic Product (GRDP). And during a period of 6 years (2010-2015) based on Local Original Revenue (PAD) inequality Riau Coastal region is higher than Riau Mainland.Keywords : Inequality Region, PDRB, PAD, Theil Entropy Index